Metode Pembelajaran Berbasis Teknologi Informasi Dalam Pengembangan Komputerisasi - Asbon Hendra Azhar; Ratih Adinda Destari; Putri Ega Sari (Jurnal TUNAS, 2021)
The development of the times can not be separated from the name Information Technology. Information Technology is very important for us, especially for the Company and for students who now have to master the information technology. Being equipped with expertise in the field of information technology will certainly help students in the future both in terms of learning at their school and in the world of work later if they after graduating from school will apply for jobs at the company. The role of computers in various fields cannot be avoided anymore. Especially in the world of education, the use of computers should be a very crucial thing. Basically, the utilization does not always require things that are very technical, but must be right on target. As well as the use of information technology in learning methods.